Análise morfológica pela microscopia eletrônica de varredura da superfície apical de dentes portadores de lesões persistentes ao tratamento endodôntico - Kill, Kleber Borgo (2009)
This study by a scanning electronic microscopy (SEM) performed a morphological assessment of apical surface of twenty root apex taken by paraendodontic surgery in teeth with periapical lesions persistent to endodontic therapy. The endodontic treatments of these teeth were satisfactory radiographycaly, and with images suggesting periapical lesions and a treatment time equals or higher than four years, or the evidence of clinical signals and/or symptoms that justified the immediate surgical intervention. After the surgical procedures, the apical segments obtained were kept in a 2.5% glutaraldehyde and stored until the analysis, the samples then were mounted on stubs, and covered in metal and observed under scanning electronic microscope. The results showed an increased occurrence of apical resorption, followed by presence of dead spaces, longitudinal root fractures and endodontic overfilling, respectively. From a perspective of the apical anatomy features, it was noted a same percentage of root apex placed apically and parapically to long axis of the root and only one-quarter of the samples presenting apical foramina. It was concluded that the morphological changes on the apical surface, the apical foramen contour and the walls of the cementum canal, both pathologic and iatrogenic nature, as well as the lack of contact of the filling material with the root canal walls contribute to the persistence of periapical infectious process postendodontic treatment.